Kenya : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes Kenya's success in boosting financial inclusion. Kenya has become a regional and global leader in mobilizing new technologies to advance financial inclusion, poverty reduction, and growth. The rapid progress of financial inclusion in Kenya has been a result of a friendly environment for the absorption of information technology, dynamic local banks, and open and stable regulations. Advances in financial inclusion over the past 10 years have allowed Kenyans to reap many of the benefits of financial access at a much faster pace than the typical cycle of financial deepening in low- and middle-income countries. Mobile financial services have lowered the transaction cost of remittances, allowing Kenyan households to smooth consumption in the face of shocks and significantly reducing poverty.